2023
DOI: 10.3390/d15080933
|View full text |Cite
|
Sign up to set email alerts
|

High Megabenthic Complexity and Vulnerability of a Mesophotic Rocky Shoal Support Its Inclusion in a Mediterranean MPA

Francesco Enrichetti,
Giorgio Bavestrello,
Valentina Cappanera
et al.

Abstract: The deep shoal of Punta del Faro (Ligurian Sea, Mediterranean Sea) is a mesophotic rocky elevation hosting complex animal forests threatened by fishing activities. To identify appropriate conservation measures and set a reference example for similar cases, we present a detailed characterization of its megabenthic communities and a quantification of the fishing pressure. The results highlight the high natural value of the area, presenting high biodiversity (111 megabenthic and demersal species) and diverse type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Proving that a species no longer exists in a given area is difficult, especially in the marine environment [176]. Frequent and intense heatwaves associated with the periods of rapid warming have caused mass mortalities of many Ligurian Sea autochthonous species [26,177,178], some of which, however, survive in deeper waters [28,179,180]. Primary productivity alteration [181], together with other dysfunctions [182] and disturbances [183], have heavily impacted the Ligurian Sea biota [28].…”
Section: Discussionmentioning
confidence: 99%
“…Proving that a species no longer exists in a given area is difficult, especially in the marine environment [176]. Frequent and intense heatwaves associated with the periods of rapid warming have caused mass mortalities of many Ligurian Sea autochthonous species [26,177,178], some of which, however, survive in deeper waters [28,179,180]. Primary productivity alteration [181], together with other dysfunctions [182] and disturbances [183], have heavily impacted the Ligurian Sea biota [28].…”
Section: Discussionmentioning
confidence: 99%
“…The density values of F. quadrangularis found in this study are comparable to or even greater than those reported in the literature; for example, 0.83 col. m −2 in the Adriatic Sea at a depth of 162 m 53 and from 54.7 to 7771.6 ind. km −2 in the northern and central Adriatic Sea 54 ; 0.05–0.35 col. m −2 mean density along the Gioia Canyon in the southern Tyrrhenian Sea 7 ; 0.00–0.08 col. m −2 in the Ionian Sea 55 ; and 0.2 col. m −2 in the Ligurian Sea (Portofino) 56 . Aggregations of this sea pen in the Mediterranean Sea are typical of hydrodynamically active areas such as the bases of ridges, slightly sloping escarpments, and continental slopes 57 .…”
Section: Discussionmentioning
confidence: 99%
“…The interest in Italian herbaria has been greatly hampered in the last two years by the foundation of the National Biodiversity Future Center (NBFC, www.nbfc.it/, accessed on 30 October 2023) aimed at conserving, restoring, monitoring, and enhancing Italian and Mediterranean biodiversity. The NBFC is one of the five national centers dedicated to frontier research, involving 48 institutions and companies throughout Italy, specifically involved in the study of biodiversity on land and water ecosystems based on key enabling technologies and environmental sustainability [47][48][49][50]. Interestingly, NBFC activities are also focused on the enhancement of Italian natural history museums with the digitization of natural collections and the development of national samples and data repositories on biodiversity.…”
Section: Botanical Collections In Italy and The Italian National Biod...mentioning
confidence: 99%